Analisis Implementasi E-business dalam Mewujudkan Green Banking di Perbankan Syariah yang Berkelanjutan - Cindi Novita Sari Cindi; Muhammad Iqbal Fasa Muhammad Iqbal Fasa; Suharto Suharto; Adib Fachri Adib Fachri (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2022)
E-business it self is a technology to develop business, both internal and external processes. Green Banking is translated as banking efforts to prioritize the fulfillment of sustainability in lending or its operational activities. The method used in this study is a qualitative descriptive analysis technique, where all data generated and presented are in the form of descriptions, namely in the form of an overview of the results of the study. The results of the study show that the implementation of e-business in Islamic banking helps to realize sustainable Green Banking, with the application of E-business in Islamic banking can increase environmental awareness.